2017
DOI: 10.1093/eurpub/ckx046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a counselling intervention to improve contraception in deprived neighbourhoods: a randomized controlled trial

Abstract: This brief counselling intervention increased the consistent use of effective contraception in low-income neighbourhoods with a high proportion of immigration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In Sweden, contraception counselling usually takes place in a one-on-one meeting, which may be a challenge for migrants from societies that are more collectivist 28. One potential approach to both increasing contraception use and decreasing unintended pregnancies may be to include both women and men in contraception counselling 29. Healthcare providers who counsel migrants have reported that cost and the presence or absence of regular bleeding are two important factors in their choice of contraception methods 30.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, contraception counselling usually takes place in a one-on-one meeting, which may be a challenge for migrants from societies that are more collectivist 28. One potential approach to both increasing contraception use and decreasing unintended pregnancies may be to include both women and men in contraception counselling 29. Healthcare providers who counsel migrants have reported that cost and the presence or absence of regular bleeding are two important factors in their choice of contraception methods 30.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was framed in an urban equity approach strengthening the health and well-being of low income communities and enhancing local community capacity. It was based in evidence [13,14,21] theory [22,23] and a qualitative research [8,15]. The program was led by community health task groups set in the neighbourhoods, linked to service provision care and supportive environments, and provided by NGO and public health workers.…”
Section: Methodsmentioning
confidence: 99%
“…All materials for users were translated and culturally adapted. Contraceptive methods effectiveness and availability, along with tailored counselling was provided in individual sessions in community facilities such as youth centres, libraries and other settings by trained public health nurses or psychologists [29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations